AKTIVITAS BERSAMA ORANG TUA-ANAK DAN PERLINDUNGAN ANAK MENINGKATKAN KESEJAHTERAAN SUBJEKTIF ANAK - Irzalinda, Vivi; Puspitawati, Herien; Muflikhati, Istiqlaliyah (Jurnal Ilmu Keluarga dan Konsumen, 2014)
In achieving better child well-being, international and Indonesia have agreed to increase efforts in the protection of children, including increasing the capacity of parents to perform better parenting. Time-shared activities among parent and children are important factor to create qualified parenting. The purpose of this study was to analyze the time-shared activities among parents-children and child protection in the family and its influence on children’s subjective well-being. This study was a cross-sectional design. Study sites were selectedpurposively at Ciputri Village, Pacet Sub District; and Sindang Jaya Village, Cipanas Sub District, Cianjur DistrictWest Java Province. One hundred and twenty families were purposively chosen among farmer families. Findingsshowed that the time-shared activities among parents-children were categorized as in low level. Child protection in physical aspect was in the low category but the environmental protection of child was in high category. Children’s subjective well-being was in the high category. Independent variables that influenced the children’s subjective well-being were time-shared activities among parents-children and physical protection. It was recommended to conduct socialization about the importance of child protection and time-shared activities amongparents-children on improving children’s subjective well-being among farmer families.